EFFECTIVE ORGANIZATION OF DISTRIBUTION CHANNELS WITH THE HELP OF ARTIFICIAL INTELLIGENCE IN THE B2B HOUSEHOLD CHEMICALS MARKET (Marketing Journal, 2025)
This study explores the role of artificial intelligence in distributing household chemical products in the B2B market. It analyzes key functions such as demand forecasting, inventory optimization, recommendation systems, and supplier selection. Based on vi sual data and scholarly sources, the findings show that AI technologies help stabilize product flow, reduce costs, and offer solutions aligned with customer needs. The results confirm that integrating AI into B2B distribution models enhances precision, fle xibility, and economic efficiency. 366
Keywords: B2B distribution; artificial intelligence; household chemicals; inventory management; demand forecasting; recommendation system; supplier selection